Características agronômicas, anatômicas e valor nutritivo do capim-elefante em diferentes idades de corte - SANCHÊS, Sâmara Stainy Cardoso (2017)
The objective of this work was to evaluate the agronomic, anatomical and nutritional value of elephantgrass (Pennisetum purpureum Schum) at different cutting ages. A completely randomized design was used, with five replications and five treatments (cut ages) totaling 25 experimental units. For the anatomical characterization the 3x5 factorial arrangement, with three levels of insertion (LI) of the leaf and leaf sheath in the tiller (apical, medial and basal) and five cut ages (30, 45, 60, 75 and 90 days). Degradation of dry matter (DM) and crude protein (CP) was estimated by in situ technique using a Santa Inês sheep. Incubation times in the ruminal environment were 6, 12, 24, 72 and 96 hours. The experimental design was completely randomized, with a 5x5 factorial arrangement (five incubation times and five treatments). There was a significant (p <0.05) from the ages of cuts for total forage production (TFP), leaf production (LP), stem production (SP), dead material (DM), living tillers (LT), dead tillers (DT) and height (H).In relation to the bromatological composition, there was a significant effect (p <0.05), with the increase in the age of cut for dry matter (DM), neutral detergent fiber (NDF), acid detergent fiber (ADF) and ash in the two evaluated fractions (leaf and stem), the crude protein (CP) content showed a significant decrease according to the increase in the cutting age with 39.83% (leaf) and 26.97% (stem) From 30 to 90 days of age. There was only significant interaction (p <0.05) in the proportion of anatomical tissue of the leaf blade, for the xylem area (XIL), where it was observed in the lower cut ages (30 and 45 days) in the apical and medial NI The highest percentage of this structure 9.21 and 10.10%, respectively. For the sclerenchyma (SCL) area of the leaf sheath, a significant interaction was observed. The area occupied by the SCL increased with the increase in maturity. The degradation parameters of DM in the two evaluated fractions decreased significantly with the increase in plant maturity. The effective degradability of CP in the leaf and stem fractions decreased significantly with the increase in the rate of passage (2, 5 and 8% / h). The highest rate of degradation (c) of CP for leaf fraction was obtained at 60 days of age (9.47% / h), already at 45 days of age (6.81%/h). The agronomic, anatomical and nutritional characteristics of elephant grass are influenced by the increase in plant maturity. The use of grass at 60 days of age implies an optimum point of production and quality